Effect of Dietary Protein and Carbohydrates on Survival and Growth in Larvae of the Henosepilachna vigintioctopunctata (F.) (Coleoptera: Coccinellidae). Issue 4 (5th July 2018) - Wang, Zai-Ling; Wang, Xiang-Ping; Li, Chuan-Ren; Xia, Zhen-Zhou; Li, Shi-Xiang
Abstract: The ratio of protein and carbohydrate in an insect's nutritional regime can significantly influence its survival, growth, and fecundity. The effects of 11 different artificial diets containing protein (p): carbohydrate (c) ratios were determined in larvae of the phytophagus ladybug, Henosepilachna vigintioctopunctata (F.) (Coleoptera: Coccinellidae). We recorded the developmental times and survival rates of the larvae and weighed their pupae. When the concentration of carbohydrates was kept constant while the concentration of proteins was increased (p29:c20, p31:c20, p33:c20, and p35:c20), H. vigintioctopunctata could successfully complete the larval and pupal stages. The highest survival rate and greatest pupal mass of H. vigintioctopunctata were 72% and 19.5 mg, respectively, when reared on the p33:c20 diet. H. vigintioctopunctata larvae, however, were unable to develop into adults when the concentration of protein remained constant while the level of carbohydrates was increased (p20:c23, p20:c25, p20:c27, and p20:c29), or when the total amount (p + c) was kept at 48% (p22:c26, p 24:c24, p26:c22). Evidently, changing the availability of quality diet, especially the total protein levels, can significantly affect the performance to H. vigintioctopunctata. Our results indicated that the maximum development and survival of H. vigintioctopunctata larvae occurred within a narrow range—when the p:c ratio was (33:20).